2020
DOI: 10.1108/ijse-03-2020-0145
|View full text |Cite
|
Sign up to set email alerts
|

Can financial inclusion reduce the presence of corruption? Evidence from selected countries in Africa

Abstract: PurposeThe purpose of this paper is to evaluate the impact of financial inclusion (FI) on control of corruption in selected African countries.Design/methodology/approachThe study employs secondary data spanning over a period of 2005–2016. These data are sourced from IMF's International Financial Statistics, World Bank Development Indicators, Global Financial Development Database, Transparency International and International Country Risk Guide. The author uses Sarma (2008) approach to construct the FI index for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…In line with theoretical prescriptions and previous empirical studies (see Adjasi et al, 2012; Ford et al, 2008; Yang, 2008), we specify the following model: Growthitgoodbreak=β0goodbreak+β1FDIitgoodbreak+β2AMLRitgoodbreak+β3FDI*AMLRitgoodbreak+β4Zitgoodbreak+μigoodbreak+vtgoodbreak+εit where Growthit represents economic growth of country i in time t . In line with previous empirical works (see Ajide, 2020; Nirola & Sahu, 2019; Polizzi et al, 2020), we measure economic growth using the growth of real GDP per capita. GDP per capita income represents the distribution of wealth within the economy as compared to the GDP growth rates.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…In line with theoretical prescriptions and previous empirical studies (see Adjasi et al, 2012; Ford et al, 2008; Yang, 2008), we specify the following model: Growthitgoodbreak=β0goodbreak+β1FDIitgoodbreak+β2AMLRitgoodbreak+β3FDI*AMLRitgoodbreak+β4Zitgoodbreak+μigoodbreak+vtgoodbreak+εit where Growthit represents economic growth of country i in time t . In line with previous empirical works (see Ajide, 2020; Nirola & Sahu, 2019; Polizzi et al, 2020), we measure economic growth using the growth of real GDP per capita. GDP per capita income represents the distribution of wealth within the economy as compared to the GDP growth rates.…”
Section: Methodsmentioning
confidence: 94%
“…where Growth it represents economic growth of country i in time t. In line with previous empirical works (see Ajide, 2020;Nirola & Sahu, 2019;Polizzi et al, 2020), we measure economic growth using the growth of real GDP per capita. GDP per capita income represents the distribution of wealth within the economy as compared to the GDP growth rates.…”
Section: Empirical Model Specificationmentioning
confidence: 99%
“…Their study of 63 countries showed a positive relation with economic growth. Ajide (2020) studied the bearing of financial inclusion on corruption in 13 African countries. The study conducted on the data from 2005 to 2016 found that achieving a threshold level of financial inclusion helps control corruption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A previous study by Setor et al (2021) confirms that digital payments contribute to corruption control in 111 developing countries, however, the authors did not identify the specific modality of digital payment (credit card, debit card, internet banking, mobile banking) that drives corruption control, nor did they consider financial inclusion in the study, which we believe is one of the relevant factors for wider use of digital payments. Likewise, Ajide (2020) shows that financial inclusion reduces corruption in 13 African countries, however, the study does not consider the relevance of financial innovation in the link between…”
Section: Introductionmentioning
confidence: 96%
“…Financial innovation, specifically digital payments, improves financial transparency, reduces information asymmetry and uncertainty, and proves to be a great opportunity to control corrupt activities (Jamil et al, 2022;Setor et al, 2021). For example, salary banking greatly reduces ghost employees and corruption (Ajide, 2020(Ajide, , 2021. Low levels of education are a major barrier to financial inclusion and innovation in Africa and other developing countries (Mukherjee and Sood, 2020).…”
Section: Introductionmentioning
confidence: 99%